PERJANJIAN ASURANSI BERDASARKAN ASPEK HUKUM - Maulid Khilmaturangga Adnan Syarif (JSE: Jurnal Sharia Economica, 2022)
Our lives will never be separated from a risk, whether related to the soul or property. Therefore, the emergence of some risk to the form and when a risk arises will arise that we can not guess before. Regarding a risk that arises suddenly a person can distance themselves, face, ignore, or use other institutions. With the concept of risk transfer and risk sharing that creates an insurance institution. There is a lot of uncertainty that we often experience in our lives. This uncertainty that we often experience has to do with fate and destiny as a human being that has been determined by God. Based on the science of law, all of this is called an event that can lead to the existence of applicable laws. In the event that can cause the existence of this law has a potential risk that may arise. For example, in the event of the death of a person who may have something to do with a husband or wife or also with their children who have a long future to go through, which can be a less pleasant consequence if there is no preparation to meet various needs to come. In this insurance agreement can serve for the transfer and distribution of risks that have positive functions, both to the community, state development, and also the company. The benefits of this insurance agreement also create a sense of peace, because it can get protection from a possibility of a bad event. For example, if there is a company that uses insurance agreements for risk transfer then the company will be able to develop its business broadly without fear of experiencing risk.